Transition in Slovenian rural areas - Lorber, Lučka (Journal for Geography, 2009)
This paper discusses the changes in Slovenian rural areas after socio-economic changes in the post-socialist European states in the 1990s. It illustrates regional and national factors having effect on transition in Slovenian rural areas. Special emphasis is put on the analysis of structural indicators of socio-economic changes in the Slovenian rural areas in comparison to the neighbouring countries. Slovenian population is strongly attached to their traditional rural way of life. When ranging people’s life values, care for maintaining the rural landscape, assuring the quality of life in relation to nature and production of healthy food come out among their highest priorities. The mentioned fact implies an elaborate analysis of interdependence between the economic impacts of trade economy and realisation of common European agricultural policy in relation to maintaining traditions of living and farm management in Slovenian rural areas. Thus, evaluation of national agricultural policy and development of rural area through indicators showing land use categories, individual farm sizes and their ownership structure, the share and mobility of rural population and individual farms’ production orientation, are a good indicator of transition in Slovenian rural area.